Development of pipette tip-based on molecularly imprinted polymer micro-solid phase extraction for selective enantioselective determination of (−)-(2S, 4R) and (+)-(2R, 4S) ketoconazole in human urine samples prior to HPLC-DAD. Issue 20 (10th May 2016) - Santos da Silva, Ricky Cássio; Mano, Valdir; Pereira, Arnaldo César; Costa de Figueiredo, Eduardo; Borges, Keyller Bastos
Abstract : A simple and selective sample preparation technique employing PT-MIP-μ-SPE coupled to HPLC/DAD was developed for the determination of the cis -enantiomers of ketoconazole in human urine samples. Abstract : In this work a simple and selective sample preparation technique employing pipette tip-based on molecularly imprinted polymer micro-solid phase extraction (PT-MIP-μ-SPE) coupled to HPLC/DAD was developed for the determination of the cis -enantiomers of ketoconazole (KTZ) in human urine samples. Several parameters affecting the proposed PT-MIP-μ-SPE technique were investigated, namely the washing solvent, type and volume of the eluent, amount of material (molecularly imprinted polymer, MIP), sample volume, pH and salt addition. The recoveries were around 100% using 5 μg mL −1 for the (−)-(2 S, 4 R ) and (+)-(2 R, 4 S ) KTZ enantiomers. Optimum chromatographic conditions for determination of the (−)-(2 S, 4 R ) and (+)-(2 R, 4 S )-KTZ enantiomers were found using the chiral stationary phase polysaccharide derived of amylose tris(3, 5-dimethylphenylcarbamate). The mobile phase consisted of ethanol : water (95 : 5, v/v) at a flow rate of 1 mL min −1 and the detection was performed at 250 nm. The performance criteria for linearity, sensitivity, precision, accuracy, recovery, robustness and stability were assessed and they were within the recommended guidelines. The method showed to be linear over the concentration range from 6.25 to 650.00 ng mL −1 for each enantiomer, with the correlation coefficients of 0.9962 and 0.9952 for (+)-(2 R, 4 S )-KTZ and (−)-(2 S, 4 R )-KTZ, respectively. Within-day and between-day precision and accuracy assays for these analytes were studied at three concentration levels and were lower than 15%. The results for the application of the method in preliminary urinary excretion showed that there are not significant differences in the analyzed concentrations of KTZ cis -enantiomers in urine samples.